On scale effects, market power and growth when human and technological capital are complements - Alberto Bucci (Fondazione Eni Enrico Mattei (FEEM), 2000)
In this paper we build an endogenous growth model where human capital and ideas are complements in the long-run equilibrium and technological progress takes the form of a continuous increase in the number of horizontally differentiated varieties of intermediate inputs. One peculiarity of the economy we analyse is that in the sectors where both kinds of capital are accumulated no externality (or spillover) effect does exist. Many insights arise from the model. First of all, due to the complementarity hypothesis, multiple steady states emerge. Secondly, growth does not depend on the scale of the economy, but turns out to be sensitive to the fraction of human capital devoted to research. Finally, when skilled work and ideas are perfect complements, product market competition is unambiguously bad for growth. eywords:
Keywords: L16; O31; O41; 330; Endogenous growth; innovation; human capital; industrial organisation; macroeconomics; Neue Wachstumstheorie; Humankapital; Industrielle Forschung; Marktmacht; Theorie